Coastal erosion assessment using remote sensing and computational numerical model. Case of study: Libertador Bolivar, Ecuador. (15th November 2021) - Nativí-Merchán, Sophia; Caiza-Quinga, Rommel; Saltos-Andrade, Ivan; Martillo-Bustamante, Carlos; Andrade-García, Gina; Quiñonez, María; Cervantes, Eduardo; Cedeño, Jonathan
Abstract: The sea-level rise has intensified the erosion of coastal zones, whereby the coastal management requires tools to evaluate and predict the dynamics of shoreline. In this paper we evaluate the impact of erosion in a coastal zone of the active margin of Ecuador, where the subduction causes vertical movements of coast. The area chosen to develop this study Playa Bruja and Libertador Bolivar beaches in which activities such as tourism, fisheries, agriculture and gastronomy are the main sources of income. This study analyzes the shoreline retreatment from 1986 to 2019, by using aerial images (remote sensing), along to selected beaches to validate a computational numerical model as MIKE Zero. This calibrated model permitted us to evaluate possible scenarios and hazards until 2025 (with or without coastal protection such as offshore breakwaters), to promote integrated coastal management for decision-makers, especially considering the possible collapse of one of the main coastal highways (E15) of Ecuador country. The result from remote sensing suggests a mean rate of erosion of 0.64 m/yr, which well-correlate with the outputs from the numerical model (between 0.4 and 0.7 m/yr). The net transport, influenced by waves, was calculated in 470m 3 /day (1.71 E +5  m 3 /yr), predominant to the north. These results allowed us to categorize three levels of erosion threat such as high (45%), medium (46%), and low (9%) and this classification allows to observe which areas are more exposed or have a higher threat and then propose alternatives to protect. Future scenarios under natural conditions show a continuous retreat of the coast that put in risk the community and hypothetic scenario under an arrangement of 5 breakwaters generates accretion next to Playa Bruja Beach but a deficient supply at the north side at Libertador Bolivar. Highlights: Aerial photographs and numerical models allows to assessment shoreline change. Multi-temporal analysis of aerial photographs allows to estimate coastal erosion rate. Limited data over the area require to apply different tools to sediment dynamics study. Coast model results can be calibrated with field data measured and aerial photographs.